Implementation of E-Learning Technology in Encouraging Independent and Flexible Learning - Dumiyati Dumiyati; Liza Husnita; Ranti Nazmi; Muh Safar; Yayat Suharyat (P3M IAI Nusantara Batang Hari, 2024)
Technology has developed significantly over time. The development of this technology cannot be stopped or hindered because it is a demand for the needs of human life which are increasing day by day. Technology drives change from various perspectives, including in the field of education. Education develops along with technological developments. With the help of innovative media and learning methods used, education can be supported by technology. With the help of educational technology can be completed anywhere and anytime. The purpose of this research is to investigate the use of e-learning technologies to promote independent and flexible learning. The method used in this study is a quantitative research method with a survey design. Data for this study were obtained by filling out a questionnaire via the Google Forms link. The results of this study are that the introduction of e-learning technology encourages independent and flexible learning, creates flexible choices available to students anywhere and anytime, which enriches learning materials and stimulates learning, opens up learning and increases efficiency. teaching and learning processes and encourage student independence. To take advantage of it, educational institutions, both schools and tertiary institutions, must apply it in a different way, complement or replace it. The limitation of this research is that researchers only conduct research at the school level. The researcher also hopes that future researchers can take this research to a higher level, and the researcher also hopes that in the future there will be other researchers who can advance this research.